2012
DOI: 10.1111/j.1365-2702.2012.04168.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethical issues of incorporating spiritual care into clinical practice

Abstract: Aims and objectives. The aim of this article was to analyse the scholarly discourse on the ethical issues of incorporating spirituality and religion into clinical practice. Background. Spirituality is an important aspect of health care, yet the secularisation of health care presents ethical concerns for many health providers. Health providers may have conflicting views regarding if and how to offer spiritual care in the clinical setting. Design. Discursive paper.Results. The discourse analysis uncovered four t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 51 publications
0
13
0
10
Order By: Relevance
“…Following on mandates of nursing codes of ethics, Fowler et al (2012) argued that the power differential in the nursepatient relationship needs to be taken into consideration when providing spiritual or religious care. Although unwelcome spiritual care would be unethical, it is recognized that failure to provide appropriate spiritual care also is unethical (Pesut & Thorne, 2007;Polzer Casarez & Engebretson, 2012;Fowler et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Following on mandates of nursing codes of ethics, Fowler et al (2012) argued that the power differential in the nursepatient relationship needs to be taken into consideration when providing spiritual or religious care. Although unwelcome spiritual care would be unethical, it is recognized that failure to provide appropriate spiritual care also is unethical (Pesut & Thorne, 2007;Polzer Casarez & Engebretson, 2012;Fowler et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…2 Also Polzer Casarez and Engebretson equate 'the totally secular side' of healthcare with 'imposing his (the physician's) views of religion (that of denial or atheism)' on the patient. 16 Similarly, Bishop accuses liberalism of viewing traditional religious practices as blocking us 'from seeing the pure principles of ethics'. 17 of spiritual care in medical contexts.…”
Section: Resultsmentioning
confidence: 99%
“…As regards the relevance of nurses focusing more on spiritual aspects in patient care, the literature [30] indicates the importance of including the spirituality domain in nursing care. Researchers [31] have identified that at least 80% of cancer patients would like to participate in spiritual care activities.…”
Section: Discussionmentioning
confidence: 99%